Cannabis use and the development of psychosis or schizophrenia, analysis of current legislation and regional mapping: A systematic review - Alves da Silva Zunini, Pablo Andres; Passamani Borges, Guilherme; Almeida Tonon, João Henrique; Nishimura, Rafaela; Barrios, Iván; O'Higgins, Marcelo; Ruíz-Díaz, Noelia; Almirón-Santacruz, José; Navarro, Rodrigo; Ventrigliio, Antonio; Torales, Julio; Sousa Martins-da-Silva, Anderson; et al. (Medicina Clínica y Social, 2022)
Introduction: The relationship between cannabis use and the onset of psychotic symptoms is sufficiently substantiated. The legalization and/or decriminalization of cannabis could increase the frequency and quantity of cannabis use among its users. Objective: This systematic review aims to summarize the findings of studies that investigated the risk, precocity and intensity of psychosis in cannabis users, taking into account the status of legalization and/or decriminalization of cannabis use in different countries. Methodology: Articles published up to May 2018 were included, in English, Portuguese and Spanish, all extracted from the PubMed and SciELO databases, respecting the inclusion and exclusion criteria. Results: 19 studies from 18 countries were included. The relationship of cannabis use and the onset of psychotic symptoms was sufficiently substantiated. However, there was no data that supported an increase in the risk, precocity or intensity of psychosis in cannabis users from countries with higher levels of legalization/decriminalization of cannabis use to the date of the present study. Conclusion: The use of cannabis is associated with the development of psychosis. So far, there is no data pointing to an increase in the precocity, risk or intensity of psychosis in cannabis users, due to the legalization or decriminalization of the use of cannabis. However, the absence of data to date does not exclude these possibilities, since none of the studies analyzed in this review specifically assessed the effects of legalization/decriminalization policies on those outcomes. Therefore, prospective studies focused on the effects of legalization or decriminalization policies should be conducted in countries such as Canada, Spain, the United States of America (some states), the Netherlands, and Uruguay.
Keywords: Psicosis; Cannabis; Legalización; Despenalización